Walking the Deckle Edge: Scribe or Author? Jayamuni and the Creation of the Nepalese Avadanamala Literature - Formigatti, Camillo A. (Buddhist Studies Review, 2017)
The article presents a preliminary survey of textual reuse in Nepalese collections of jatakas and avadanas, focusing in particular on three works: the Avadanasataka, the Divyavadana, and the Dvavimsatyavadanakatha. The reassessment of the manuscript tradition of these three Sanskrit collections, based on Nepalese manuscripts and Tibetan translations, sheds more light on the role of scribes in the creation of these collections and of the Nepalese avadanamala literature. In particular, the great role played in the 17th century by the Nepalese scribe and scholar Jayamuni in shaping the text of the Avadanasataka, the Divyavadana, and many other Buddhist narrative works is brought to light. The result of this preliminary survey shows that a study of this type of collections based on the available critical editions should be rethought in the light of the specific character of their manuscript and textual transmission in medieval and early modern Nepal.